Myxomycetes within ecotones in temperate and tropical forests - Rojas-Alvarado, Carlos (2021)
Ecotones are interesting portions of forests where microorganisms can be studied for monitoring and diversity purposes. Given the faster life cycle of these organisms, their study in such a context is important to develop models that allow us to understand adaptive microbial dynamics. The main objective of this study was to evaluate the dynamics of myxomycetes present in the leaf litter layer in different geographical locations representing both temperate and tropical systems, using an experimental approach within the ecotones produced by sharp forest edges. Employing the moist chamber technique and three ecological indicators (species richness, diversity, and number of records, as a proxy for abundance) associated with the reproductive phase of the life cycle of myxomycetes, the present study summarized the potential effect of both temperate and tropical ecotones on the distribution of these organisms. Data from 26 locations in six countries showed that all indicators were higher in temperate than in tropical forests and that most differences could be explained by ecological effects. The overall influence of the ecotone on myxomycetes was opposite in temperate and tropical forests, but the data collected for both types of forests showed similarities that could be explained by comparable mathematical models. These results suggested that, with the methods used herein, ecotones do affect ecological patterns of myxomycetes, but the intensity and directionality of such an effect differ depending on the forest type involved.